African Geranium (Pelargonium sidoides) in the Treatment of Acute Respiratory Tract Infections: A Review of Mechanisms of Action, Efficacy, and Clinical Applications - Kwasniewska, Anna; Wiśniewska, Aleksandra; Dąbek, Jakub; Kosucka, Wiktoria; Balik, Dominik; Lara, Joanna; Grabowska, Martyna; Grabowska, Karolina; Kaszyńska, Karolina; Kubicka, Jagoda (Journal of Education, Health and Sport, 2025)
Introduction: African geranium (Pelargonium sidoides) is a plant endemic to the mountainous regions of South Africa, traditionally used for centuries to treat respiratory infections and gastrointestinal disorders. The main active ingredient is an extract from the roots and rhizomes, designated as EPs 7630, which contains coumarins, coumarin glycosides, phenolic acids, flavonoids, fatty acids, and proanthocyanidins. Modern phytotherapy utilizes this extract to treat acute respiratory infections such as bronchitis, tonsillitis, and the common cold. Aim of the study: The aim of this work is to present the mechanisms of action and efficacy of African geranium in the treatment of acute respiratory infections, with particular emphasis on its antiviral, antibacterial, and immunomodulatory properties. The study synthesizes available scientific research to evaluate the therapeutic potential of EPs 7630 as an alternative to conventional therapies. Materials and methods: The article was prepared by analyzing multiple databases, including PubMed, Google Scholar, and Elsevier, covering the period from 1995 to 2024. Conclusions: African geranium, thanks to its antiviral, antibacterial, and immunomodulatory properties, represents an effective and safe option for treating acute respiratory infections. Clinical trials confirm its efficacy in reducing the duration and severity of illness, making it a valuable alternative to conventional therapies. However, further research is needed to determine optimal dosing and long-term effects of the preparation